Diagnostic, therapeutic, and prognostic implications of the 2021 World Health Organization classification of tumors of the central nervous system - Gritsch, Simon; Batchelor, Tracy T.; Gonzalez Castro, L. Nicolas (Cancer, 2022)
The 2016 revised fourth edition of the World Health Organization (WHO) classification of central nervous system (CNS) tumors incorporated molecular features with histologic grading, revolutionizing how oncologists conceptualize primary brain and spinal cord tumors as well as providing new insights into their management and prognosis. The 2021 revised fifth edition of the WHO classification further integrates molecular alterations for CNS tumor categorization, updating current understanding of the pathophysiology of many of these disease entities. Here, the authors review changes in the new classification for the most common primary adult tumors—gliomas (including astrocytomas, oligodendrogliomas, and ependymomas) and meningiomas—highlighting the key genomic alterations for each group classification to help clinicians interpret them as they consider therapeutic options—including clinical trials and targeted therapies—and discuss the prognosis of these tumors with their patients. The revised, updated 2021 WHO classification also further integrates molecular alterations in the classification of pediatric CNS tumors, but those are not covered in the current review. The 2021 World Health Organization classification of tumors of the central nervous system increasingly relies on molecular alterations for central nervous system tumor categorization. The new classification will help improve diagnosis, prognosis, and treatment selection (including enrollment into relevant clinical trials) for patients with brain tumors.